Transition to Diagnosis-Related Group Payments for Health : Lessons from Case Studies - Bredenkamp, Caryn; Bales, Sarah; Kahur, Kristiina (Washington, DC: World Bank, 2019)
This book examines how nine different health systems--U.S. Medicare, Australia, Thailand, Kyrgyz Republic, Germany, Estonia, Croatia, China (Beijing) and the Russian Federation--have transitioned to using case-based payments, and especially diagnosis-related groups (DRGs), as part of their provider payment mix for hospital care. It sheds light on why particular technical design choices were made, what enabling investments were pertinent, and what broader political and institutional issues needed to be considered. The strategies used to phase in DRG payment receive special attention. These nine systems have been selected because they represent a variety of different approaches and experiences in DRG transition. They include the innovators who pioneered DRG payment systems (namely the United States and Australia), mature systems (such as Thailand, Germany, and Estonia), and countries where DRG payments were only introduced within the past decade (such as the Russian Federation and China). Each system is examined in detail as a separate case study, with a synthesis distilling the cross-cutting lessons learned. This book should be helpful to those working on health systems that are considering introducing, or are in the early stages of introducing, DRG-based payments into their provider payment mix. It will enhance the reader's understanding of how other countries (or systems) have made that transition, give a sense of the decisions that lie ahead, and offer options that can be considered. It will also be useful to those working in health systems that already include DRG payments in the payment mix but have not yet achieved the anticipated results.